2018
DOI: 10.1186/s12885-018-5080-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of cachexia in adult cancer patients: a systematic review of clinical trials

Abstract: BackgroundCachexia is a multisystem syndrome characterized by weight loss, anorexia, loss of muscle mass, systemic inflammation, insulin resistance, and functional decline. Management of cachexia involves addressing multiple underlying biological mechanisms. Previous review on pharmacological management of cancer cachexia identified progestins and corticosteroids as effective agents for treatment of cachexia. However, to date no consensus exists on a single effective or standard treatment for management of cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 51 publications
(100 reference statements)
0
79
0
13
Order By: Relevance
“…In particular, the identification of several endogenous factors functioning as mediators of CC and the uncovering of their relative mechanisms of action has led to the achievement of important frontiers in this field of oncology. This has allowed the development of potential effective pharmacological agents for the clinical management of this metabolic syndrome (31). Intriguingly, we now know that several of these effectors share the same or similar metabolic effects, and that most often they exhibit synergic effects when administered together.…”
Section: Mediators Of Cc: What Have We Learned From In Vitro and In Vmentioning
confidence: 99%
“…In particular, the identification of several endogenous factors functioning as mediators of CC and the uncovering of their relative mechanisms of action has led to the achievement of important frontiers in this field of oncology. This has allowed the development of potential effective pharmacological agents for the clinical management of this metabolic syndrome (31). Intriguingly, we now know that several of these effectors share the same or similar metabolic effects, and that most often they exhibit synergic effects when administered together.…”
Section: Mediators Of Cc: What Have We Learned From In Vitro and In Vmentioning
confidence: 99%
“…Studies over the past few decades have identified several mediators of cancer cachexia; however, none of the drugs designed to target these preclinical candidates showed efficacy in clinical trials for the treatment of cancer-associated cachexia in many cancer types, including PDAC [20]. To address the challenges associated with identifying and targeting the mediators of cancer cachexia, our laboratory recently demonstrated that the metal ion transporter Slc39a14 (Zip14) is upregulated in cachectic muscles in the context of metastatic colon, lung, and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other agents have already reached clinical trials, such as myostatin inhibitors [120], the appetite stimulant megestrol acetate [121], testosterone [122], antimyostatin antibody [123], and monoclonal antibody (MABp1) [124], showing the influence of these drugs in different aspects of the spectrum of cancer cachexia. Recently, a combination of drugs to treat patients with cancer cachexia has been tested [125]. On the other hand, some compounds, including thalidomide, produced side effects that may outweigh their potential benefits [126].…”
Section: Treatment Perspectivementioning
confidence: 99%